Legal pluralism and empires, 1500-1850 - Benton, Lauren A., 1956-; Ross, Richard Jeffrey (UPCC book collections on Project MUSE. History., 2013)
Historians used to imagine empire as an imperial power extending total domination over its colonies. Now, however, they understand empire as a site in which colonies and their constitutions were regulated by legal pluralism: layered and multicentric systems of law, which incorporated or preserved the law of conquered subjects. By placing the study of law in diverse early modern empires under the rubric of legal pluralism, this book offers both legal scholars and historians a framework for analyzing the complex and fluid legal politics of empires. Contributors analyze how ideas about law moved across vast empires, how imperial agents and imperial subjects used law, and how relationships between local legal practices and global ones played themselves out in the early modern world. The book's tremendous geographical breadth, including the British, French, Spanish, Ottoman, and Russian empires, gives readers the most comparative examiniation of legal pluralism to date.